The interethnic imagination roots and passages in contemporary Asian American fiction - Rody, Caroline, 1960- (New York ; Oxford : Oxford University Press, 2010)
Rody proposes a new paradigm for understanding the changing terrain of contemporary fiction. She claims that what we have long read as ethnic literature is in the process of becoming 'interethnic'. Examining an extensive range of Asian American fictions, she offers readings of three especially compelling examples.
Description based on print version record.
Includes bibliographical references and index.
Keywords: American fiction -- Asian American authors -- History and criticism; Asian Americans in literature; Ethnic relations in literature; Racially mixed people in literature; Cultural fusion in literature